EXPLOITATION OF COMPLEX OIL LAYERS IN OIL FIELDS - Bekjonov Rozisher Soatmurodovich; Soyibov Yorkul Uktamjon ugli; Ruzatov Bunyod Fakhriddin ugli (Bright Mind Publishing, 2025)
The only factor explaining the difference between these two straight sections is that during the period characteristic of each of them, the density of the well pattern was compacted. As is known, one of the main parameters that allows us to evaluate the effectiveness of hydrodynamic methods is the number of recoverable reserves and the final oil recovery factor.
Keywords: Mining, alignment, well, traction, netting, compression, removable backup, coverage, dynamics, evaluation, effectiveness.